The Effect of Corporate Governance Mechanisms on Earnings Management in Manufacturing Companies Listed on the Indonesia Stock Exchange - Pratama Putra, Andjast; Nuryaman, Nuryaman (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Earnings management is an action taken from the choice of several accounting policies that exist in the company to achieve certain goals. The corporate governance mechanism is a good governance system as a system that regulates the relationship between the role of the board of commissioners, the role of directors, shareholders and other stakeholders. One of the world's failures to create a healthy, clean and responsible business life is earnings management. This study aims to find out more about earnings management in manufacturing companies listed on the Indonesia Stock Exchange. The type of research used is explanatory . The research population is Manufacturing companies listed on the Indonesia Stock Exchange as many as 296 companies. The results of the study are the independence of the board of commissioners, managerial ownership, institutional ownership and audit committee competence have a negative effect on earnings management.